Christian-Muslim relations in the Anglican and Lutheran Communions : historical encounters and contemporary projects - Grafton, David D.; Duggan, Joseph F.; Harris, Jason Craige (Palgrave pivot., 2013)
In a time in which Islamophobia has become common, and many public discussions have focused upon either terrorist activities of Muslims or the implementation of sharia in the United States, little attention has been given to actual inter-faith engagement and practice among Christian and Muslim communities. Anglicans and Lutherans have a long history, and a wide variety of experiences from which to draw and reflect in responding to both simplistic interpretations of Islam and vitriolic rhetoric against Muslims. This work seeks to provide vignettes of Muslim-Christian engagement within the Anglican and Lutheran experiences from around the world. This work does not look to reduce Christian-Muslim relationships to a least common denominator of religious pluralism or civic religion. Rather, it provides thoughtful Anglican and Lutheran responses to these relationships from a variety of perspectives and contexts, and lays the groundwork for ongoing thoughtful, faithful, sensitive, and sincere engagement between Christians and Muslims.